Strategic opportunities and future directions for ecotourism development in Uzbekistan: A case study of the Termiz region - Djurayeva Dilnoza; Hakimova Mehriniso (E3S Web of Conferences)
Ecotourism is an emerging sector that offers significant potential for sustainable development in Uzbekistan. The Termiz region, located in the southern part of the country, is particularly promising due to its diverse landscapes, such as the Tien Shan foothills, and rich cultural heritage, including historical sites like the ancient city of Termiz. To achieve this, the research analyzes current ecotourism activities, infrastructure needs, and regulatory frameworks while emphasizing the importance of community engagement. The study utilizes qualitative methods, including field surveys and stakeholder interviews, to gather insights on the existing challenges and opportunities. Key findings indicate that there is a need for eco-friendly infrastructure development, improved regulatory support, and greater investment in conservation efforts. Additionally, promoting Termiz's unique cultural heritage and natural landscapes through targeted marketing strategies could significantly boost the region's ecotourism potential. The conclusions highlight that adopting sustainable tourism practices and fostering community involvement are essential for creating a thriving ecotourism sector in Termiz. By implementing these strategies, policymakers and stakeholders can not only support environmental conservation but also contribute to the socio-economic development of the region, making Termiz a key destination for ecotourism in Uzbekistan.